2006
DOI: 10.1159/000091655
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage Incidence among Whites, Blacks and Caribbean Hispanics: The Northern Manhattan Study

Abstract: American blacks and Hispanics may have a greater incidence of subarachnoid hemorrhage (SAH) than whites, but incidence data are scant. We used an active hospital and community surveillance program and autopsy reports to identify incident SAH cases among white, black and Hispanic adults living in Northern Manhattan between July 1993 and June 1997. The annual incidence adjusted for age and sex to the 1990 US Census was 9.7 per 100,000 (95% CI 7.5–12.0). Compared with whites (9 cases, age- and sex-adjusted annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 17 publications
2
46
1
5
Order By: Relevance
“…5 In that review, the pooled age-adjusted incidence rate of aSAH in low-to middle-income countries was found to be almost double that of high-income countries. 5 Although some reports have suggested the incidence of aSAH in the United States to be 9.7 per 100 000, 6 the 2003 Nationwide Inpatient Sample provided an annual estimate of 14.5 discharges for aSAH per 100 000 adults. 7 Because death resulting from aSAH often occurs before hospital admission (an estimated 12% to 15% of cases), 8,9 the true incidence of aSAH might be even higher.…”
Section: Incidence and Prevalence Of Asahmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In that review, the pooled age-adjusted incidence rate of aSAH in low-to middle-income countries was found to be almost double that of high-income countries. 5 Although some reports have suggested the incidence of aSAH in the United States to be 9.7 per 100 000, 6 the 2003 Nationwide Inpatient Sample provided an annual estimate of 14.5 discharges for aSAH per 100 000 adults. 7 Because death resulting from aSAH often occurs before hospital admission (an estimated 12% to 15% of cases), 8,9 the true incidence of aSAH might be even higher.…”
Section: Incidence and Prevalence Of Asahmentioning
confidence: 99%
“…60 Others have shown that case fatality rates decreased from 57% in the mid-1970s to 42% in the mid-1980s, 11 whereas rates from the mid-1980s to 2002 are reported to be anywhere from 26% to 36%. 6,12,13,18,20,61,62 Mortality rates vary widely across published epidemiological studies, ranging from 8% to 67%. 59 Regional variations become apparent when numbers from different studies are compared.…”
Section: Natural History and Outcome Of Asahmentioning
confidence: 99%
“…Exclusion of 2 studies 12,14 which did not report 1-month outcomes, and 1 study with an exceptionally low case-fatality rate of 8%, 39 did not substantially alter the results. Eighteen studies including our own 11,13,[21][22][23][24][25][27][28][29][31][32][33]35,37,38 reported the mean age of cases with SAH and proportion of women. After adjustment for age and sex, there was a similar but nonsignificant reduction in case-fatality of 0.9% per annum (Ϫ0.2 to 2.0%, p ϭ 0.10).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…4,12 In the United States, the incidence is 9.7 per 100,000 population. 4,13 The median case fatality rate (CFR) in the US was 32.2% and has declined over the last three decades; the CFR is higher in Europe and lower in Japan.…”
Section: Epidemiology Outcomes Of Aneurysmal Sahmentioning
confidence: 99%